‘Twitch Interviews’: teaching innovation in audiovisual journalism: Interviews with Radio and TV Professionals - Alcudia Borreguero, Mario; Cervera Barriga, Esther (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The format of the live audiovisual interview, through the Twitch livestream platform, becomes an effective and invaluable tool when it comes to learning journalistic skills and deepening the informative task through professional experiences, thanks to the testimonies of prominent radio and television communicators. also showing his human side. In addition, the training contents of the subject Audiovisual Journalism of the Degree in Journalism of the CEU San Pablo University are updated. A collaborative methodology in which students participate in writing and conducting interviews.